If a real function
satisfies the equation above for all real
, then compute the value of
If the answer is of the form , find
Take as a constant.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Assuming f ( x ) is differentiable over x , y ∈ R , let us differentiate this functional equation with respect to x and y:
3 1 ⋅ f ′ ( 3 x + y ) = 2 f ′ ( x ) = 2 f ′ ( y ) ⇒ f ′ ( x ) = f ′ ( y ) = A ⇒ f ( x ) = A x + B (i).
Substituting (i) back into the original functional equation results in:
A ( 3 x + y ) + B = 2 1 ⋅ [ A x + B + A y + B ] ⇒ ( 3 A ) ( x + y ) = ( 2 A ) ( x + y ) ⇒ A = 0
Hence, our required function must be constant: f ( x ) = B , B ∈ R . The final integration produces ∫ f ( 2 x 9 ) d x = ∫ B d x = B x with L = M = N = 1 and ⌊ 1 0 0 0 M + 2 9 N + 8 L ⌋ = 1 0 3 7 .